Thermal behavior of Zefreh dolomite mine (Central Iran) - Shahraki B.K.; Mehrabi B.; Dabiri R. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Dolomite has a large amounts of MgO and is an important raw materials for steel, iron and refractory industries. In this paper thermal behavior of Zefreh dolomite at various temperatures was studied by differential thermal analysis (DTA), Thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FT - IR) and powder X-ray diffraction (XRD) techniques. The DTA curve shows two endothermic peaks at 772 and 834ºC. The first peak is associated with the formation of magnesia (MgO), calcite(CaCO3) and CO2. The second peak represents the decomposition of calcite with formation of CaO and further CO2 release. At 772ºC quantitative XRD analysis in atmospheric condition shows small amounts of CaO (less than 2%) which form simultaneously or later than calcite. TGA curve shows total weight loss for decomposition of dolomite is 46.2%. By increasing heating time of samples in furnace, dolomite decomposes in lower temperatures. X-ray diffraction analysis of heat treated samples up to 750ºC indicates that dolomite structure changes into calcite. The increases in quartz content accelerated the mechanochemical deformation and amorphization of dolomite phase. At high temperature ( more than 1000ºC) Ca3Mg(SiO4)2 and CaSiO4 were formed. XRD and FTIR confirm dolomite decomposition reactions.